Sabre‐sheath trachea: An underused diagnostic weapon in the thoracic armoury. Issue 1 (6th July 2021) - Brassil, Colm; Srigandan, Shrivuthsun; Murray, Conor P
Abstract: Introduction: A sabre‐sheath trachea is a highly specific sign for chronic obstructive pulmonary disease. It also correlates well with the degree of disease. We hypothesized that the term is vastly under‐utilized in radiologic reporting, despite its high diagnostic value. Methods: We interrogated our multisite metropolitan‐wide radiology information system to find the number of CT reports containing the phrase 'sabre‐sheath trachea' and conceivable variants thereof, over the 10 years to present. We compared this with the entire number of CT chest reports in the same time period in order to estimate the utilization of the sign. Results: The results confirmed our hypothesis that the sign is rarely invoked, likely around 1 in 41 times relative to opportunity. Conclusions: This highly specific sign of chronic obstructive small airway disease should be reinforced in training and utilized by radiologists.